Subspace-Based Method for Multiple-Target Localization Using MIMO Radars - Wei Xia; Zishu He; Yuyu Liao (2007 IEEE International Symposium on Signal Processing and Information Technology, 2007)
The concept of multiple-input-multiple-output (MIMO) radar is recently proposed inspired by recent advances in MIMO communications. The subspace-based method for multiple-target localization is proposed in this paper. It is shown that the "effective source" covariance matrix is almost always nonsingular under mild conditions in the MIMO radar configuration. The performance of the proposed method is validated by numerical simulations.